Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Sturt L.) di Tanah Inceptisol pada Berbagai Dosis KCl - Anwar, Khairul; Alpandari, Heny (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Sweet corn (Zea mays saccaharata Sturt L.) is a plant that is harvested when it is young and widely cultivated in tropical areas. However, production is still low, so it needs to be optimized with fertilization. This research aimed to determine the effect of KCl fertilizer doses on the growth and yield of sweet corn (Zea mays saccharata Sturt L.) plants in inceptisol soil. It was carried out on the Rendole Pati Palawija Nursery Development Garden grounds. This research used a Single Factor Complete Randomized Block Design (RAKL) experimental experiment with 3 treatments, namely: 0 kg/ha (K0), 75 kg/ha (K1), and 150 kg/ha (K2). Data were analyzed using analysis of variance (ANOVA). The research results showed that the dose of KCl fertilizer significantly affected the parameters of plant height, fresh weight of stover, dry weight of stover, ear diameter, ear length, and sweetness content. The best growth and production of sweet corn is at a dose of 150 kg/ha.